Generating electricity in a solid oxide fuel cell decarbonization methods - A. A. Filimonova; A. Y. Vlasova; R. F. Kamalieva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Determination of effective methods of carbon dioxide capture and utilization, search for promising solutions and testing of carbon dioxide capture methods at a laboratory facility. The most popular absorption methods of CO2 capture, in which the gas reacts with a liquid absorbent.METHODS. The laboratory setup includes the CO2 source itself (gas cylinder), an absorber, and a flask with sodium hydroxide solution to analyze absorption efficiency. Efficiency is evaluated by the titrimetric method, where a solution of hydrochloric acid is used as a titrant, phenolphthalein and methyl orange act as indicators.RESULTS. For the analysis, available absorbents were selected, which are available at most thermal power plants. As a result of a laboratory experiment, it was found that a quicklime suspension of 6% has the highest sorption capacity.CONCLUSION. The decarbonization of the industrial energy sector is a complex process that requires global changes in fuel policy, namely the transition to carbon-free energy resources. An alternative energy resource is hydrogen energy, but even here carbon dioxide emissions are present. Capture and disposal will help decarbonize the main sources of pollution. Industrial carbon dioxide capture has great potential, which lies in the variety of uses of sorption materials.